Implementing Spatial Planning Based on Environmental Sustainability in the Mining Area - Luthfi Marfungah; Rachmad Safa’at; Istislam, Istislam; Indah Dwi Qurbani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The problem of finite mineral and coal natural resources has been reopened by the growing demand for development and mining resources, which impacts the global arena. Environmental issues are just one of the issues caused by mining activities, which are another. In mining sites, there has to be an ongoing planning process based on the environment. This study addresses the existing mining regulatory framework and the problem of harmonization between spatial plans for mining regions based on environmental sustainability, with a particular emphasis on spatial planning for mining sites in Indonesia. Under the provisions of spatial planning, this article outlines the fundamental concepts of strategic environmental sustainability as a roadmap for sustainable growth in the mining industry. This study concludes that the idea of creating a mining business permit area is predicted to function as a tool for prevention against the emergence of significant environmental pollution and damage due to mining activities with the existence of an integrated concept of environmental licensing and spatial planning. Because this authority can be determined based on the size of "geographical-ecological", "economical", or "administrative" conditions, recommendations made with the existence of legal criteria relating to the determination of mining areas to become the authority of the Minister of Environment and Spatial Planning, Governors, and Regents/Mayors will result in the principle of environmental sustainability.